2019
DOI: 10.1371/journal.pone.0213034
|View full text |Cite
|
Sign up to set email alerts
|

Human roars communicate upper-body strength more effectively than do screams or aggressive and distressed speech

Abstract: Despite widespread evidence that nonverbal components of human speech (e.g., voice pitch) communicate information about physical attributes of vocalizers and that listeners can judge traits such as strength and body size from speech, few studies have examined the communicative functions of human nonverbal vocalizations (such as roars, screams, grunts and laughs). Critically, no previous study has yet to examine the acoustic correlates of strength in nonverbal vocalisations, including roars, nor identified reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 107 publications
(182 reference statements)
4
42
2
Order By: Relevance
“…Human postures modified from ref. 23. success the upper body strength of male vocalizers (32), especially from roaring as opposed to, for example, screaming vocalizations (33). The current results add to this literature that peripheral upper limb movements imprint their presence on the human voice as well, providing an information source about dynamically changing bodily states.…”
Section: Discussionsupporting
confidence: 55%
“…Human postures modified from ref. 23. success the upper body strength of male vocalizers (32), especially from roaring as opposed to, for example, screaming vocalizations (33). The current results add to this literature that peripheral upper limb movements imprint their presence on the human voice as well, providing an information source about dynamically changing bodily states.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, in humans, no previous study has examined whether individual differences in F0 are preserved across the broad range of human vocal sounds, from modal and emotionally valenced speech to nonverbal vocalizations. While it is possible that idiosyncratic differences in F0 between different vocalizers might be overridden by the more extreme F0 modulations that characterize agonistic and distress vocalizations, existing data on the F0 profiles of human grunts [15], roars [16], laughs and cries [19] indicate that such vocalizations retain a degree of sexual dimorphism, wherein men produce relatively lower-pitched vocalizations than do women. There is also preliminary evidence that within each sex, F0 in modal speech correlates with F0 in sung speech [20], and that cues to individual identity are retained in valenced human speech [21], laughter [22], cries [23], and in the screams of both humans ( [24], cf.…”
Section: Introductionmentioning
confidence: 99%
“…Low pitched male voices are linked to larger body size, especially weight and height, to a particular body shape (shoulder and chest circumference, shoulder-to-hip ratio) (Evans et al, 2006), and arm strength (Puts et al, 2011). Nevertheless, a recent meta-analysis had shown that compared to other vocal parameters, voice pitch is not a reliable predictor of height in adults of the same sex (Pisanski et al, 2014) and it is a poor predictor of body weight, shape, and strength (Collins, 2000; Collins and Missing, 2003; Bruckert et al, 2006; Evans et al, 2006; Sell et al, 2010; Vukovic et al, 2010; Pisanski et al, 2016; Raine et al, 2019).…”
Section: Introductionmentioning
confidence: 99%